Pengaruh Live Streaming Shopping dan Online Customer Review terhadap Keputusan Pembelian: (Studi pada Mahasiswa Universitas Darul Ulum Islamic Centre Sudirman) - Pitaloka Dharma Ayu; Fajar Suryatama; Sri Rahayu (Jurnal Ekonomi Manajemen Akuntansi, 2024)
Shopee, as one of the e-commerce platforms in Indonesia, provides live streaming and online customer review features to increase interaction and product information. This research aims to determine the effect of live streaming and online customer reviews on purchasing decisions among Shopee users among Darul Ulum Islamic Center Sudirman University students. The research method used is quantitative with an associative approach. The research sample consisted of 100 respondents using a purposive sampling technique. The data collection technique was carried out using a questionnaire distributed via Google Forms. The research results show that live-streaming shopping and online customer reviews significantly positively influence purchasing decisions among Shopee users among students at Darul Ulum Islamic Center Sudirman University. The adjusted R square value is 0.588. This shows that the independent variables in this research (live streaming shopping and online customer reviews) can explain the dependent variable (purchase decisions) by 58.8%.